PENGARUH BIAYA OPERASIONAL DAN PENDAPATAN TERHADAP KINERJA KEUANGAN (STUDI KASUS PERUSAHAAN PERDAGANGAN ECERAN YANG TERDAFTAR DI BEI PADA TAHUN 2019-2023) - Nindy Dwi Sepfutri; Amsah Hendri Doni (BORJUIS: JURNAL OF ECONOMY, 2024)
This research is motivated by the formation of instability in operational costs, income and financial capacity. and if operational costs increase until financial capacity decreases. And if income increases until financial capacity increases. This research intends to identify and analyze how much impact operational costs and income have on financial capacity (case study of street trading companies listed on the IDX for the period 2019-2023). The type of research used is a quantitative method and the type of information is inferior information. The illustration collection method used in this research is a purposive sampling method with a total of 32 industries. The information analysis method uses descriptive statistical experiments, classical assumption experiments consisting of normality experiments, multicollinearity experiments, heteroscedasticity experiments, autocorrelation experiments, multiple linear regression experiments consisting of experiments (R2), and hypothesis testing. The results of this research partially prove that the elasticity of operational costs has a significant effect on financial ability as evidenced by the results of the experiment tcount≥ttable (3.415≥1.3043) with significant figures showing ≤0.05. Income elasticity has a significant effect on financial ability as evidenced by the results tcount≥ttable (- 3.740≤1.3043) with significant figures 0.001≤0.05. Operational costs and income simultaneously have a significant effect on financial ability as evidenced by fcount and ftable (6.996≥3.25) with significant figures 0.003≤0.05.